Scanning of Optical Fields Using Near-Field Scanning Optical Microscopy - Pudis, Dusan; Martincek, Ivan; Turek, Ivan; Michalka, M.; Kovac, jr., J.; Gottschalch, V.; Kacik, Daniel (Communications - Scientific letters of the University of Zilina, 2006)
The Near-field scanning optical microscopy is a high-resolution diagnostics for the optical field characterization. In our experiments we focus on the optical field characterization of semiconductor laser diodes based on multiple quantum well structure as well photonic crystal fibers. The parameters of optical field of laser diode in the near- and far-field zone as well the local spectral analysis of the quantum well laser devices in the near-field will be studied. The mode distribution across photonic crystal fiber was scanned using near-field scanning optical microscopy. This experimental technique in combination with an analysis of optical field in the near-field region could be an effective optical tool for the final diagnostics of laser devices and photonic crystal fibers.